The Influence of Human Resource Management on Job Satisfaction among Primary Healthcare Providers: A Descriptive Study - Garima Jain; Vikram Bisen; Sanjay K. Singh (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Job satisfaction among primary healthcare practitioners is essential for providing effective and high-quality treatment. Human resource management (HRM) techniques are crucial in determining work satisfaction by affecting motivation, retention, and productivity. Materials and Methods: A descriptive, cross-sectional research was performed with 150 primary healthcare practitioners from diverse settings. Data were gathered using a standardized questionnaire consisting of 30 topics pertaining to HRM procedures, including recruiting, training, performance assessment, remuneration, and work environment. Job satisfaction was assessed on a standardized Likert scale. Descriptive and inferential statistics, including correlation and regression analysis, were used to examine the data. Results: The research indicated that 70% of participants had moderate to high levels of work satisfaction. Training and development opportunities had the greatest satisfaction score (mean = 4.2 ± 0.5), while remuneration received the lowest happiness score (mean = 3.1 ± 0.7). A significant positive association was identified between HRM practices and total work satisfaction (r = 0.65, P < 0.01). Regression analysis revealed that work environment (β = 0.35, P < 0.001) and performance assessment (β = 0.28, P < 0.01) were the most significant determinants of job satisfaction. Conclusion: Effective human resource management methods are essential for improving work satisfaction among primary healthcare professionals. It is advised that interventions aimed at enhancing training, equitable remuneration, and supportive workplace conditions be implemented to cultivate a motivated and content staff, hence elevating the quality of patient care.